2018
DOI: 10.2134/age2018.07.0016
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of Variation from Vegetation Index for Sugarcane Population and Stalk Evaluation

Abstract: Core Ideas• Variety and planting material affect cane population and millable stalk production.• Coefficient of variation from sensor readings decreases as cane canopy closes.• Cane varieties for sugar and energy production differ greatly in canopy structure.• Canopy structure influences sensor-based profiling of cane population and stalk. ABSTRACT Coefficient of variation (CV) is a statistical measure of variability in data. This study was conducted to evaluate the relationship of CV computed from Vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Subsequently, spatial variance also gradually increased during autumn and winter after crop harvesting. This inverse relationship between the spatial variability (CV) of VIs and VIs values was consistent with previous findings (Martin et al 2007;Chanda et al 2018).…”
Section: Resultssupporting
confidence: 93%
“…Subsequently, spatial variance also gradually increased during autumn and winter after crop harvesting. This inverse relationship between the spatial variability (CV) of VIs and VIs values was consistent with previous findings (Martin et al 2007;Chanda et al 2018).…”
Section: Resultssupporting
confidence: 93%
“…The results of the analysis of variance showed significant variation in the seed yield and yield components of 150 soybean genotypes (Table 1). The high coefficient of variation (CV) indicated much variability in data [27] among HLs, particularly in the characters of the number of branches, in the number of empty pods, and in wet and dry biomass. ** = significant at 1 % probability level (P < 0.01), * = significant at 5 % probability level (P < 0.05), ns = not significant, CV = coefficient of variation, HS = 100 seed weight (g), FD = days to flowering, MD = days to maturity, G/V = generative/vegetative ratio, PH = plant height (cm), NB = number of branches/plant, NN = number of nodes/plant, FP = number of filled pods/plant, EP = number of empty pods/plant, WB = wet biomass (t/ha), DB = dry biomass (t/ha), HI = harvest index, S/P = weight of seed/plant (g).…”
Section: Resultsmentioning
confidence: 99%
“…The differences observed among cane varieties were also noticed in the conventional method of satellite data processing. For instance, Lofton et al [ 86 ] and Chanda et al [ 87 ] corroborated that spectral reflectance can vary among varieties due to differences in canopy architecture. The three varieties considered in the current study varied considerably in their morphology [ 38 ], which could explain the observed differences.…”
Section: Discussionmentioning
confidence: 99%